Analisis Penentuan Profesi Infolahta Prajurit TNI Angkatan Laut Menggunakan Metode Profile Matching - Arya Aji Kusuma; Rodiah Rodiah (AGUSPATI Research Institute, 2023)
Kasatker Disinfolata (Navy Information and Data Processing Service) is an institution in the Indonesian Armed Forces engaged in the field of information and data processing. This institution is a professional supervisor of personnel who handle information and data processing. As an adviser for the infolahta profession, the task is to plan, prepare, implement, control and evaluate the assignment of infolahta professional personnel. In realizing consistency in control of the infolahta profession within the Indonesian Navy, it is necessary to reform and organize the infolahta profession personnel in the form of personnel coaching. The problem that will be faced at this time is that there is no data that states the infolahta profession. To support these needs requires a decision support system to facilitate the determination of infolahta profession soldiers. For research using the Profile Matching method as a decision support system. Based on three criteria, namely general education, service in infolahta and military education in terms of Specialist Development Education (Dikbangspes). From the results of this study resulted in a form in the form of personnel recommendations with the highest value from each profile target